Serological differentiation of Citrus tristeza virus isolates in India - P. RAMACHANDRAN*, A. ROY and (Indian Phytopathology, 2003)
Studies on differentiation of Citrus tristeza virus isolates from four locations in the country were undertaken using polyclonal (CREC-1052), monoclonal (MCA-13) and orange stem pitting (aSP) strain (CH 110/R1 09) antibodies. All the four isolates viz. CTV-B, CTV-D, CTV-N and CTV-P were found severe strain of CTV using polyclonal as well as monoclonal antibodies. It was found that the four isolates were of severe type as they gave positive reaction with monoclonal MCA-13. Whereas with asp Abs, only CTV-B gave positive reaction while the three other isolates did not show any reaction both in glasshouse and field samples. The paper constitutes the first record of serological evidence for the detection of asp strain in CTV population in the country.